Sexual Orientation Equality in Schools Teacher Advocacy and Action Research - Holt, Matthew; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
This book explores how to help teachers become better advocates for sexual orientation equality in secondary schools. Examining this issue through the lens of qualitative emancipatory action research, a group of Australian teachers embarked on a journey of teacher advocacy. Critical theory has long highlighted teachers as key players in either challenging dominant social narratives, or else perpetuating oppressive systems of power through traditional forms of education. Despite this important role, the life stories of teachers, which contributed to the development of their beliefs and behaviours about sexual orientation are rarely considered in the development of anti-discriminatory policy, designing the curriculum and most importantly, in teacher training. This book suggests and frames a model for advocacy, whereby teachers engage with their personal beliefs about sexual orientation, with their role as a teacher, and commit to advocacy through action by promoting student safety, challenging heteronormative narratives and role modelling compassionate behaviours in their school environments. Matthew Holt is Senior Research Advisor at the Behavioural Insights Team, UK. He is a graduate of the University of Melbourne, where he conducted the research detailed in this book for his PhD thesis.
1 Introduction to Sexual Orientation Inequality in Australia -- 2 Sexual Orientation Inequality in Schools -- 3 Sexual Orientation Equality in Schools -- 4 Critical Theory -- 5 Social Transformation -- 6 Research with Teachers -- 7 Engaging with Inequality -- 8 Engaging as a Teacher -- 9 Promoting Safety -- 10 Modelling -- 11 Conclusion.
Keywords: Sex; Ethnology; Philosophy of mind; Self; Teachers$1 (BTraining of.s; Educational sociology; Gender Studies; Sociocultural Anthropology; Philosophy of the Self; Teaching and Teacher Education; Sociology of Education